Donation of School Supplies as an Effort to Increase the Spirit of Learning for Students Affected by Flood Disasters in Garut City - Hasbi Taobah Ramdani; Asep Nizar F; Andhika Lungguh Perceka; Desy Syswianti; Sri Yekti Widadi; Wieda Widyatri Qarragita (PT FORMOSA CENDEKIA GLOBAL, 2022)
Disasters are a series of events that can threaten human life in various places, one of which is in Garut Regency which is an area with the Indonesia Disaster Prone Index ranked third in West Java Province, and one of the school facilities affected by the flood disaster in July 2022 is SDN 1 Sukaratu. This community service activity was carried out in July 2022 by providing school supplies for high school students whose homes were affected by flooding. The results of the evaluation, both questions and answers and observations of affected students, can carry out learning activities with their new equipment.